2022
DOI: 10.3390/ijerph192315918
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bisphenol A Substitutes, Bisphenol S and Bisphenol F, and Its Association with Developing Obesity and Diabetes Mellitus: A Narrative Review

Abstract: Bisphenol A, a well-known endocrine-disrupting chemical, has been replaced with its analogs bisphenol S (BPS) and bisphenol F (BPF) over the last decade due to health concerns. BPS and BPF are present in relatively high concentrations in different products, such as food products, personal care products, and sales receipts. Both BPS and BPF have similar structural and chemical properties to BPA; therefore, considerable scientific efforts have investigated the safety of their exposure. In this review, we summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…BPA is ubiquitously present in the environment, air, water, soil, animal feed, wildlife, and humans [ 141 , 142 , 143 ]. While the role of direct BPA exposure in the development of diabetes mellitus and obesity has been explored extensively [ 144 , 145 ], there is a gap in the research on the prenatal effect of BPA on liver pathologies. This study was performed to address causal relationships between prenatal BPA and liver steatosis, as human studies can only point to association and not causality.…”
Section: Discussionmentioning
confidence: 99%
“…BPA is ubiquitously present in the environment, air, water, soil, animal feed, wildlife, and humans [ 141 , 142 , 143 ]. While the role of direct BPA exposure in the development of diabetes mellitus and obesity has been explored extensively [ 144 , 145 ], there is a gap in the research on the prenatal effect of BPA on liver pathologies. This study was performed to address causal relationships between prenatal BPA and liver steatosis, as human studies can only point to association and not causality.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies on BPA and analogues focus mainly on BPA as an obesogen. Very few human studies have analysed the effect of analogues (Alharbi et al, 2022). Exposure to low doses of bisphenols has been associated with weight gain, altered carbohydrate and lipid homoeostasis, and an effect on brain regions involved in food intake (Boucher et al, 2016) (Verbanck et al, 2017) (Heindel and Blumberg, 2019).…”
Section: Scientific Evidencementioning
confidence: 99%
“…Several studies suggest that BPA has endocrine-disrupting properties and that it can be implied in the pathogenesis of a variety of human diseases mostly affecting reproductive systems [2,3], similar to other environmental pollutants [4], as well as cardiovascular systems [5]. In this frame, epidemiological studies reported that there is an association between exposure to BPA and an increased prevalence of cardiovascular diseases (CVDs), including atherosclerosis [6], coronary and peripheral artery disease [7,8], myocardial infarction [9], and angina pectoris [10], as well as their risk factors, such as hypertension [11] and diabetes [12]. At the basis of the pathogenesis of these illnesses, a pivotal role is played Toxics 2023, 11, 391 2 of 18 by oxidative stress, endothelial activation, and dysfunction, which the latter represents the early step in the development and progression of atherosclerosis [13].…”
Section: Introductionmentioning
confidence: 99%